Increasing availability of lower energy meals vs. energy labelling in virtual full-service restaurants: two randomized controlled trials in participants of higher and lower socioeconomic position - Lucile Marty; Sasha M. Reed; Andrew J. Jones; Eric Robinson (BMC, 2021)
Abstract Background There are a range of interventions designed to promote healthier food choices in full-service restaurants. However, it is unclear how these interventions affect dietary choices in people of lower and higher socioeconomic position (SEP). Methods A total of 2091 US participants recruited online completed Study 1 (n = 1001) and Study 2 (n = 1090). Recruitment was stratified by participant highest education level, resulting in higher SEP and lower SEP groups. In a between-subjects design, participants made hypothetical food choices (main dish, plus optional sides and desserts) from six restaurants menus in the absence vs. presence of menu energy labelling and from menus with baseline (10%) vs. increased availability (50%) of lower energy main dishes. Data were collected and analysed in 2019. Two studies were conducted in order to examine replicability and generalisability of findings across different restaurant menu types. Results Across both studies, increasing the availability of lower energy main menu options decreased the average energy content of the ordered main dish (− 129 kcal, 95% CI [− 139; − 119]) and total energy ordered (− 117 kcal, 95% CI [− 138; − 95]) in both higher and lower SEP participants. Energy labelling significantly reduced the energy content of ordered main dishes in higher SEP participants (− 41 kcal, 95% CI [− 54; − 29]), but not lower SEP participants (− 5 kcal, 95% CI [− 22; 11]). However, energy labelling reduced total energy ordered (− 83 kcal, 95% CI [− 105; − 60]) irrespective of SEP. Conclusions In two virtual experiments, increasing the availability of lower energy restaurant main menu options impacted on main menu dish choice and decreased total energy ordered irrespective of SEP. Energy labelling had a less pronounced effect on total energy ordered and had a larger impact on the energy content of main menu dish choice in higher as opposed to lower SEP participants. Trial registration Clinicaltrials.gov NCT04336540 retrospectively registered (7 April, 2020).